Bio-efficacy of Unmanned Aerial Vehicle based spraying to manage pests - PARMAR, R P; SINGH, S K; SINGH, M (The Indian Journal of Agricultural Sciences, 2021)
An agricultural spraying system for UAV platform was developed at the Department of Farm Machinery and Power Engineering, Punjab Agricultural University, Ludhiana during 2019 to spray pesticides in cotton, rice and moong crops for the control of pests. The developed aerial spraying system was operated at three flying speeds, i.e. S1 (2.0 m/s), S2 (3.0 m/s) and S3 (4.0 m/s) and at three flying heights, i.e. H1 (0.50 m), H2 (0.75 m) and H3 (1.0 m). Whitefly and brown plant hopper (BPH) were the targeted pest and its bio-efficacy data were collected after spray application. Results indicated that flying height and forward speed had significant effect on bio-efficacy in all the three crops. In cotton, whitefly populations varied between 19.00-21.40 per three leaves. The maximum percent, i.e. 84.85% reduction in white fly population was observed at 7 DAS in H1S1 treatment. In rice, BPH population was varied between 6.60-9.47 per hill followed by control 17.20 per hill. Maximum percent reduction in BPH population was observed 67.42% at 7 DAS in H3S1 treatment. In moong, reduction in whitefly population was varied between 4.87-5.80 per plant followed by control (7.00 per plant). After three days of spray, combination of flying heights (H1, H2 and H3) and forward speeds (S1, S2 and S3) were found to be significantly effective in dropping whitefly and BPH population. Increase in flying height and forward speed reduced percentage reduction of pests. Combination of flying heights H1 and H2 and forward speeds S1 and S2 treatments were found significantly effective in controlling pests in all three crops.